Aero engine compressor cooling by water injection - Part 2: Performance and emission reductions - Block Novelo, David Alejandro; Igie, Uyioghosa (Elsevier, 2018)
Take-off and climb up to 3000 ft are the flight segments in which the aero-engine experiences the highest operating temperatures, which are known to be accompanied by a high production rate of Nitrogen Oxides (NOx). This contaminant has negative health implications on the human population, vegetation and wildlife that is in frequent proximity or exposure. Water injection into the compressor offers the possibility of reducing NOx. Nevertheless, limited studies have focused on the emissions reduction potentials and the wider questions of the influence of engine type and of wide-ranging ambient conditions. This study continues from Part 1 and explores the implications of the studied ambient conditions on the overall respective engine systems and their consequent emission reduction. An in-house gas turbine performance simulation software has been implemented to model and simulate the engine performance. For the emissions estimation, correlations were made from the information provided by the Engine Emissions Data Bank to quantify the reductions in Nitrogen Oxides. The 2 and 3-spool engine models investigated demonstrated significant reductions in compressor discharge and turbine inlet temperatures due to water injection. In this condition, the rotational speeds of the compressors are seen to be reduced to counter the mass flow augmenting effect of water injection and to satisfy the fixed thrust constraint. This along with lower compressor specific work brings about an improvement in the specific fuel consumption (5.3% and 7.8%, respectively) and general performance at low and high ambient temperatures. A higher advantage was seen for the 3-spool engine over the 2-spool as shown. Significant reductions in Nitrogen Oxide emissions of over to 50% are also demonstrated.
Keywords: Nitrogen oxides; Compressor cooling; Aero engine; Performance; Water injection